Present situation of Gazipur Upa-Sahar Ltd. (on basis of real estate sector of Bangladesh) - Islam, Md. Azharul (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2016.